Phosphorus Allocation to Leaves of Beech Saplings Reacts to Soil Phosphorus Availability - Meller, Sonia; Frossard, Emmanuel; Luster, Jörg (Frontiers in Plant Science, 2019)
Decreasing phosphorus (P) concentrations in leaves of beech (Fagus sylvatica L.) across Europe raise the question about the implications for forest health. Considering the distribution of beech forests on soils encompassing a broad range of nutrient availability, we hypothesized that this tree species exhibits high phenotypic plasticity allowing it to alter mass and nutrient allocation in response to local nutrient availability. To test this, we grew two groups of 12 to 15 year old beech saplings originating from sites with high and low soil P availability for two years in mineral soil from their own site and in soil from the other site. After two growing seasons, P concentrations in leaves and stem, as well as mass allocation to leaves and fine roots were affected by both soil and plant origin. By contrast, relative P allocation to leaves and fine roots, as well as P concentrations in fine roots, were determined almost entirely by the experimental soil. Independent of the P nutritional status defined as average concentration of P in the whole plant, which still clearly reflected the soil conditions at the site of plant origin, relative P allocation to leaves was a particularly good indicator of P availability in the experimental soil. Furthermore, a high plasticity of this plant trait was indicated by a large difference between plants growing in the two experimental soils. This suggests a strong ability of beech to alter resource allocation in response to specific soil conditions.